Physical soil atributes in different coffee management systems in the southern region of Espirito Santo - Thomazini, André; Azevedo, Humberto Carlos Almeida de; Pinheiro, Patrick Leal; Mendonça, Eduardo de Sá (Coffee Science - ISSN 1984-3909, 2014)
Espirito Santo state is the second largest coffee arabica producer and the largest canephoracoffee producer in Brazil. Coffee culture is responsible for a large part of the family income of 67% of the state farmers. Generally, production is based in monoculture systems showing advanced soil degradation stage. The objective of this study is to evaluate the effects of different coffee management sytems under some physical soil attributes. The work was conducted in 6 family agriculture properties and two native forests where conilloncoffee is handled through different systems. In this study were used compound soil samples obtained from two layers (0 to 10 and 10 to 20cm). Were determined granulometry, loss of horizon A, water dispersed clay, flocculation level, soil and particle densities, total porosity, aggregates stability and average geometric diameters of the aggregates. Agroecological management systems presented lower clay dispersion and higher flocculation levels. For this type of management, soil density and particle levels presented values closer to the reference forests. Aggregates were down to 47% less stable in farmings that use weeding in relation to the ones that use mowing. Weeding use consequently exposes soil to weather actions and increases soil degradation potential throughout the years, reducing its physical quality.